Cost-effectiveness of bivalent versus monovalent vaccines against hand, foot and mouth disease. (March 2020) - Liu, D.; Leung, K.; Jit, M.; Yu, H.; Yang, J.; Liao, Q.; Liu, F.; Zheng, Y.; Wu, J.T.
Abstract: Objectives: Enterovirus 71 (EV71) and coxsackievirus A16 (CA16) were responsible for 43.3% (235 123/543 243) and 24.8% (134 607/543 243) of all laboratory-confirmed hand, foot and mouth disease (HFMD) cases during 2010–2015 in China. Three monovalent EV71 vaccines have been licensed in China while bivalent EV71/CA16 vaccines are under development. A comparative cost-effectiveness analysis of bivalent EV71/CA16 versus monovalent EV71 vaccination would be useful for informing the additional value of bivalent HFMD vaccines in China. Methods: We used a static model parameterized with the national HFMD surveillance data during 2010–2013, virological HFMD surveillance records from all 31 provinces in mainland China during 2010–2013 and caregiver survey data of costs and health quality of life during 2012–2013. We estimated the threshold vaccine cost (TVC), defined as the maximum additional cost that could be paid for a cost-effective bivalent EV71/CA16 vaccine over a monovalent EV71 vaccine, as the outcome. The base case analysis was performed from a societal perspective. Several sensitivity analyses were conducted by varying assumptions governing HFMD risk, costs, discounting and vaccine efficacy. Results: In the base case, choosing the bivalent EV71/CA16 over monovalent EV71 vaccination would be cost-effective only if the additional cost of the bivalent EV71/CA16 compared with the monovalent EV71 vaccine is less than €4.7 (95% CI 4.2–5.2). Compared with the TVC in the base case, TVC increased by up to €8.9 if all the test-negative cases were CA16-HFMD; decreased by €1.1 with an annual discount rate of 6% and exclusion of the productivity loss; and increased by €0.14 and €0.3 with every 1% increase in bivalent vaccine efficacy against CA16-HFMD and differential vaccine efficacy against EV71-HFMD, respectively. Conclusions: Bivalent EV71/CA16 vaccines can be cost-effective compared with monovalent EV71 vaccines, if suitably priced. Our study provides further evidence for determining the optimal use of HFMD vaccines in routine paediatric vaccination programme in China.